Tuning the Emission of Homometallic Dyiii, Tbiii, and Euiii 1-D Coordination Polymers with 2,6-Di(1h-1,2,4-Triazole-1-Yl-Methyl)-4-R-Phenoxo Ligands: Sensitization Through the Singlet State - Aravena-Ponce, D; Aravena-Ponce, D (American Chemical Society, 2023)
This work reports the structural characterization and photophysical properties of DyIII, TbIII, and EuIII coordination polymers with two phenoxo-triazole-based ligands [2,6-di(1H-1,2,4-triazole-1-yl-methyl)-4-R-phenoxo, LRTr (R = CH3; Cl)]. These ligands permitted us to obtain isostructural polymers, described as a 1D double chain, with LnIII being nona-coordinated. The energies of the ligand triplet (T1) states were estimated using low-temperature time-resolved emission spectra of YIII analogues. Compounds with LClTr present higher emission intensity than those with LMeTr. The emission of TbIII compounds was not affected by the different excitation wavelengths used and was emitted in the pure green region. In contrast, DyLMeTr emits in the blue-to-white region, while the luminescence of DyLClTr remains in the white region for all excitation wavelengths. On the other hand, EuIII compounds emit in the blue (ligand) or red region (EuIII) depending on the substituent of the phenoxo moiety and excitation wavelength. Theoretical calculations were employed to determine the excited states of the ligands by using time-dependent density functional theory. These calculations aided in modeling the intramolecular energy transfer and rationalizing the optical properties and demonstrated that the sensitization of the LnIII ions is driven via S1 → LnIII, a process that is less common as compared to T1 → LnIII © 2023 American Chemical Society